Deskripsi Kompetensi Pedagogik Instruktur Program Pelatihan di LKP Kota Serang Banten - Siregar, Herlina; Widiansyah, Subhan; Darmawan, Dadan (Journal of Nonformal Education and Community Empowerment, 2020)
Pedagogic competencies include the ability to understand training participants, design and implement learning, evaluate learning outcomes, and develop training participants to actualize their various potentials. This study aims to describe the pedagogic competence of training program instructors in LKP Serang Banten City. This study used a qualitative approach and descriptive methods. The location of this research was LKP Anita and Ghea Serang City. Data collection techniques using interviews, documentation and observation. The research subjects were LKP managers and instructors. The results showed that pedagogic competence has an important role in managing learning and making the class conducive to learning strategies and methods that have been prepared in the lesson plan by taking into account the characteristics of the training participants.